The Relationship among Gross Barter Terms of Trade, Exchange Rates, and Economic Growth: A Case in Turkey - Ergin, Ayşe; Yetiz, Filiz (International Journal of Economics and Financial Issues, 2017)
The terms of trade are related to the measurement of foreign trade performance in open economies and are based on the comparison of export and import price ratios of a country. Since the definition of terms of trade lacks an interpretation regarding export and import volumes, calculation of gross barter terms of trade which takes the amounts into account is brought out. In this study, the relationship of gross barter terms of trade with foreign exchange rates and Industrial Production Index representing economic growth is analyzed in Turkey between 2005: 01 - 2015: 06 by using the ARDL Boundary Test approach. Keywords: Terms of Trade, Gross Barter Terms of Trade, ARDL Boundary Test approach JEL Classifications: B17, F02, F43, O44